Mongolia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper analyzes the main determinants of inflation in Mongolia using empirical tests based on a structural model approach and vector autoregression model, with a view to assessing whether inflation is predominantly affected by commodity prices or by money supply developments. Simulation and impulse response analyses are used to estimate components of the inflation dynamics under various exogenous shocks. The paper also addresses the mineral wealth management issues faced by Mongolia, and describes the mining sector and its envisaged development over the medium term.